On the heterogeneity of terror - Krisztina Kis-Katos; Helge Liebert; Günther G. Schulze (Institute for the Study of Labor (IZA), 2012)
The existing literature on the determinants of terrorism treats terror as a uniform phenomenon and does not distinguish between different types of terror. This paper explicitly addresses the heterogeneity of terror by classifying groups according to their ideologies. We show that the pattern of terror and its determinants differ strongly for different types of terror. We analyze determinants of domestic and international terrorism, for target and origin using the Global Terrorism Database and show that there have been major shifts in terror activity and composition over time.
urn:nbn:de:101:1-201305294495
Keywords: D74; K4; 330; terrorism; terror groups; heterogeneity; Politische Gewalt; Ideologie; Welt